2004
DOI: 10.1002/jmv.20115
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus in a rural community in Zimbabwe: The impact of HIV co‐infection on HPV genotype distribution

Abstract: Cervical cancer is a leading cause of cancer-related deaths in developing countries, and the human papillomavirus (HPV) is linked etiologically to cervical cancer. Hence, a vaccine which prevents HPV-associated cervical cancer would have the most impact in developing countries, including the African continent. The type-specific immune response towards HPV virus-like particles, in combination with geographical variation in the prevalence of HPV, necessitates the presence of multiple HPV type antigens in a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
54
4
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 19 publications
16
54
4
1
Order By: Relevance
“…Human papillomavirus-52, HPV-35, and HPV-58 were the most prevalent types in the present study. A high prevalence of these HPV types has been also observed in other African studies (Gravitt et al, 2000;Castellsague et al, 2001;De Vuyst et al, 2003;Mayaud et al, 2003;Xi et al, 2003;Baay et al, 2004;Thomas et al, 2004;Wall et al, 2005).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Human papillomavirus-52, HPV-35, and HPV-58 were the most prevalent types in the present study. A high prevalence of these HPV types has been also observed in other African studies (Gravitt et al, 2000;Castellsague et al, 2001;De Vuyst et al, 2003;Mayaud et al, 2003;Xi et al, 2003;Baay et al, 2004;Thomas et al, 2004;Wall et al, 2005).…”
Section: Discussionsupporting
confidence: 74%
“…Positive HPV samples were typed by LiPA and by sequencing when LiPA was inconclusive, leaving no sample unidentified. While the epidemiology of genital HPV types has been relatively better studied in Southern and Eastern African countries such as Kenya (Temmerman et al, 1999;De Vuyst et al, 2003), Malawi (Miotti et al, 1996), Mozambique (Castellsague et al, 2001), Tanzania (Mayaud et al, 2003), Uganda (Serwadda et al, 1999), and Zimbabwe (Gravitt et al, 2002;Baay et al, 2004), data from Western Africa have been scarce. The prevalence of HPV infection and associated cervical lesions have been studied in Ivory Coast (La Ruche et al, 1998) and Mali (Bayo et al, 2002), but detailed HPV types were only reported from Senegal (Xi et al, 2003), Nigeria (Thomas et al, 2004), and The Gambia (Wall et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in IARC HPV Prevalence Surveys in India and China it was considered socially unacceptable to invite unmarried women Dai et al, 2006;Li et al, 2006;Wu et al, 2007). In some earlier studies from subSaharan Africa, HPV prevalence also remained high (Kuhn et al, 2000;Thomas et al, 2004;Wall et al, 2005) or even increased (Xi et al, 2003) in middle and old age, whereas peaks in young women were reported by other investigators (Serwadda et al, 1999;Womack et al, 2000;Castellsagué et al, 2001;De Vuyst et al, 2003;Baay et al, 2004). With respect to the relative importance of different HPV types, HPV16 was the commonest type overall, that is, 13.9%, 17.7% and 48.6%, respectively, in cytologically normal and abnormal women and in women with ICC (Clifford et al, 2005;Smith et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…These neoplasms are responsible for extensive morbidity and mortality. In Zambia and other subSaharan nations, cervical cancer is the most common cancer (Baay et al, 2004;Hawes et al, 2003;Xi et al, 1998Xi et al, , 2003. Although in Africa, public education campaigns about STDs and condoms have been instituted in urban areas, there has been little success in poorer rural areas (Agha and Kusanthan, 2003).…”
Section: Epidemiology Of Hpv and Hiv/aidsmentioning
confidence: 99%